2014
DOI: 10.1002/eji.201344245
|View full text |Cite
|
Sign up to set email alerts
|

Exacerbated experimental arthritis in Wiskott–Aldrich syndrome protein deficiency: Modulatory role of regulatory B cells

Abstract: Patients deficient in the cytoskeletal regulator Wiskott–Aldrich syndrome protein (WASp) are predisposed to varied autoimmunity, suggesting it has an important controlling role in participating cells. IL-10-producing regulatory B (Breg) cells are emerging as important mediators of immunosuppressive activity. In experimental, antigen-induced arthritis WASp-deficient (WASp knockout [WAS KO]) mice developed exacerbated disease associated with decreased Breg cells and regulatory T (Treg) cells, but increased Th17 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 47 publications
0
25
0
Order By: Relevance
“…Regulatory B cells suppress the activation and differentiation of CD4 + , CD8 + , and NKT cells primarily by releasing anti-inflammatory cytokines IL-10 and TGF-β (Mauri and Ehrenstein 2008). B10 cells can also promote Foxp3 + Treg cell induction and inhibit Th1 and Th17 cell proliferation during acute inflammation (Bouma et al 2014). …”
Section: Introductionmentioning
confidence: 98%
“…Regulatory B cells suppress the activation and differentiation of CD4 + , CD8 + , and NKT cells primarily by releasing anti-inflammatory cytokines IL-10 and TGF-β (Mauri and Ehrenstein 2008). B10 cells can also promote Foxp3 + Treg cell induction and inhibit Th1 and Th17 cell proliferation during acute inflammation (Bouma et al 2014). …”
Section: Introductionmentioning
confidence: 98%
“…It has been shown that Breg deficiency and dysfunction is associated with multiple inflammatory disorders, such as autoimmune thrombocytopenia, ulcerative colitis, systemic lupus erythematosus, and experimental arthritis . Therefore, in this study, we examined the Breg cells in human patients with atherosclerosis and CAD.…”
mentioning
confidence: 99%
“…5 A recent study reported an increase in Th17 cells in WAS knockout (KO) mice, which was associated with exacerbated arthritis. 6 However, T follicular helper (Tfh) cells, a CD4…”
Section: Introductionmentioning
confidence: 99%